2008
DOI: 10.1039/b808190e
|View full text |Cite
|
Sign up to set email alerts
|

An environmentally benign and catalytically efficient non-pyrophoric Ni catalyst for aqueous-phase reforming of ethylene glycol

Abstract: A non-pyrophoric Ni catalyst (NP Ni) was prepared by alkali leaching of a Ni 50 Al 50 alloy using only ~1/10 of the amount of NaOH required for the preparation of the conventional Raney Ni catalyst. Characterizations reveal that the as-prepared NP Ni catalyst can be looked at as a Ni-Al(OH) 3 composite catalyst with Ni in the metallic state and Al(OH) 3 in forms of gibbsite and bayerite. After 100 h on stream in aqueous-phase reforming (APR) of ethylene glycol, phase transformation of gibbsite and bayerite to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…27 It has been reported that this remaining Al species could modify the chemisorption properties of reactant molecules. 28,29 The lower activity and selectivity on Raney Ni-40 reflects the detrimental effect of residue Ni-Al alloy, which prevents the selective activation of NAH bond. Hereafter, we focused our following study on Raney Ni-300 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…27 It has been reported that this remaining Al species could modify the chemisorption properties of reactant molecules. 28,29 The lower activity and selectivity on Raney Ni-40 reflects the detrimental effect of residue Ni-Al alloy, which prevents the selective activation of NAH bond. Hereafter, we focused our following study on Raney Ni-300 catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Different types of catalysts were applied in the APR of ethylene glycol, including noble metal-based catalysts, such as Pt, Pd, Rh, Ru, and Ir (Liu et al, 2008;Skoplyak et al, 2009;Kim et al, 2011;, Sn modified Raney Ni , NiMgAl layered double hydroxide catalysts, Ni/Sn/Al hydrotalcite derived catalysts (Pan et al, 2012), rapidly quenched skeletal Ni (Xie et al, 2006), non-pyrophoric Ni catalysts (Zhu et al, 2008), and Co/ZnO catalysts (Chu et al, 2011).…”
Section: Aqueous-phase Reforming Of Ethylene Glycolmentioning
confidence: 99%
“…5b. It was found that the peaks located at 73.7 and 66.9 eV, which were assigned to Al 2p level [30] and Ni 3p level [31], severely attenuated when large quantities of Ce were added. This attenuation could be ascribed to the heavy coverage by Ce as shown in the SEM characterization.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…It was found that the Ce and Ni concentrations in the liquid effluent were 29 and 62 wppm, respectively, indicating that the gradual deactivation of the catalyst was partly attributed to the Ce and Ni leaching. In addition, the gradual deactivation was also likely to be ascribed to sintering [31], the interactions between catalyst and water (e.g., oxidation by water) during the reaction [38,39] and catalyst loss during the recycling of the catalyst [14].…”
Section: Reusability Of the Catalystmentioning
confidence: 99%